2020
DOI: 10.3389/fpsyt.2020.586222
|View full text |Cite
|
Sign up to set email alerts
|

Facing Loneliness and Anxiety During the COVID-19 Isolation: The Role of Excessive Social Media Use in a Sample of Italian Adults

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) prompted people to face a distressing and unexpected situation. Uncertainty and social distancing changed people's behaviors, impacting on their feelings, daily habits, and social relationships, which are core elements in human well-being. In particular, restrictions due to the quarantine increased feelings of loneliness and anxiety. Within this context, the use of digital technologies has been recommended to relieve stress and anxiety and to decrease lonelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
171
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 208 publications
(225 citation statements)
references
References 116 publications
14
171
1
6
Order By: Relevance
“…Our results only partially confirmed these hypotheses. As expected, participants declared they spent more time on SNSs during the pandemic, particularly women, thus supporting previous results showing an increase in the hours per day spent using social media during the pandemic ( 31 ). Furthermore, our findings are aligned with all the previous results concerning the association between FoMO and PSNSU [e.g., ( 41 , 46 )] as FoMO directly predicted PSNSU.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results only partially confirmed these hypotheses. As expected, participants declared they spent more time on SNSs during the pandemic, particularly women, thus supporting previous results showing an increase in the hours per day spent using social media during the pandemic ( 31 ). Furthermore, our findings are aligned with all the previous results concerning the association between FoMO and PSNSU [e.g., ( 41 , 46 )] as FoMO directly predicted PSNSU.…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, the positive central role of a recreational and needful use of videogames and SNSs in times of physical and social distancing, has been evidenced even though carefully addressed ( 27 , 28 ), also suggesting that an excessive use of SNSs might temporarily act as a coping strategy ( 29 , 30 ). However, some authors have recently argued that this coping mechanism might potentially lead to a longer-lasting threat (i.e., Problematic Social Networking Sites Use; PSNSU) in keeping with findings from a few recent studies ( 31 , 32 ).…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Fourth, the amount of time spent daily on social media searching for and reading information on COVID-19 was associated with increases in psychological distress. A previous study reported that people spend more time on social media during the COVID-19 pandemic compared to social media usage before the pandemic [50] and that people who excessively use social media for COVID-19 information are more likely to experience increases in feelings of fear and in symptoms of anxiety [40,50]. Social media is an easily accessible platform for information dissemination and acquisition, particularly during periods of social distancing and stay-at-home orders.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the link between people’s experience of fear of COVID-19 and feelings of loneliness has received little research attention. Although physical distancing measures have been critical in containing the rate of infection, there is concern that limits on social activities and restrictions on in-person social contacts may increase feelings of loneliness [ 26 , 27 ]. Prior research on the experience of loneliness in response to the social restrictions due to the COVID-19-related quarantine reported mixed findings.…”
Section: Introductionmentioning
confidence: 99%